273 Supplementation of Organic and Inorganic Selenium on Stress of Weaned Pigs. 1. Growth Performance and Immune Responses. (10th April 2018) - Doan, N; Ji, P; Kim, K; Bravo, D; Liu, Y
Abstract: Supplementing selenium (Se ) could boost immune responses against certain pathogens. The objective of this experiment was to evaluate different sources of Se supplements on growth performance and immunity of weaned pigs in response to diquat injection. Thirty-five crossbred pigs (9.72 ± 1.39 kg) were individually housed and randomly assigned to one of five treatments, including a negative control (NC ) and a positive control (PC ), in which pigs were fed a basal diet without or with diquat injection. The basal diet was not supplemented with any Se. Pigs in the other 3 treatments were fed with the diets supplemented with 0.3 mg/kg of selenium from sodium selenite, Se yeast, or soybean protein chelated Se. The experiment lasted 17 days, including 10 days before and 7 days after diquat injection. In the PC and Se groups, all pigs were intraperitoneally injected with diquat at 10 mg/kg BW on day 11. Pigs in the NC group were intraperitoneally injected with sterile 0.9% saline. Pigs were weighed at d 0, 10, and 17 and daily feed allotments were also recorded to calculate feed efficiency and growth performance. Blood samples were collected at 0 h (prior to injection), 6 h, 24 h, 2 d, 4 d, and 7 d post-injection (PI ) for analysis of complete blood count and plasma cortisol. All data were analyzed using the PROC MIXED of SAS with a randomized complete block design. Diquat injection reduced ( P < 0.05) ADG (181 vs. 707 g/d) and ADFI (399 vs. 826 g/d) from d 0 to 7 PI when pigs were fed with the basal diet. Supplementation of Se did not affect growth performance of pigs compared with the PC. Diquat injection increased ( P < 0.05) plasma cortisol and the population of white blood cells and neutrophils. Compared with the PC, pigs supplemented with all 3 types of Se products reduced ( P < 0.05) white blood cell (12.49, 12.86, and 12.36 vs. 17.54 10 3 /µL) and neutrophils (7.77, 8.34, and 7.78 vs. 11.42 10 3 /µL) at 6 h PI, while supplementation of soybean protein chelated Se decreased ( P < 0.05) lymphocytes (5.89 vs. 8.89 10 3 /µL) at 4 d PI. The addition of all 3 types of Se reduced ( P < 0.05) plamsa cortisol concentration, compared with the PC. In conclusion, dietary supplementation of any of 3 Se products at 0.3 mg/kg enhanced systemic inflammatory response and reduced stress of weaned pigs induced by chemical injection.